2023
DOI: 10.1093/aob/mcad008
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of hygrophytic plant species in the Anatolia–Caucasus region: insights from phylogenomic analyses ofCardamineperennials

Abstract: Background and Aims Southwestern Asia is a significant centre of biodiversity and a cradle of diversification for many plant groups, especially xerophytic elements. In contrast, little is known about the evolution and diversification of hygrophytic flora. To fill this gap, we focus on Cardamine (Brassicaceae) species that grow in wetlands over a wide altitudinal range. We aimed to elucidate their evolution, assess the extent of presumed historical gene flow between species, and draw inference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 102 publications
1
20
0
Order By: Relevance
“…This is the most widespread, genetically and morphologically complex species among the Cardamine hygrophytes in Southwestern Asia. The centres of its distribution and genetic diversity are in northern Anatolia and the Caucasus (Kantor & al., 2023 and present results), which provide favourable ecological conditions with numerous peaks reaching into the (sub)alpine zone and high humidity from the adjacent Black and Caspian Seas even during climatic oscillations (Parolly, 2020). We found that its genetic variation in northeastern Anatolia is highly structured geographically, with four adjacent but allopatric clades (Anat A–Anat D) revealed from the targeted nuclear genes.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…This is the most widespread, genetically and morphologically complex species among the Cardamine hygrophytes in Southwestern Asia. The centres of its distribution and genetic diversity are in northern Anatolia and the Caucasus (Kantor & al., 2023 and present results), which provide favourable ecological conditions with numerous peaks reaching into the (sub)alpine zone and high humidity from the adjacent Black and Caspian Seas even during climatic oscillations (Parolly, 2020). We found that its genetic variation in northeastern Anatolia is highly structured geographically, with four adjacent but allopatric clades (Anat A–Anat D) revealed from the targeted nuclear genes.…”
Section: Discussionsupporting
confidence: 61%
“…Divergence time estimates suggested that this lineage originated in the late Pliocene (Kantor & al., 2023), and we assume that it had a broader range encompassing both the Balkans and western Anatolia. The restricted gene flow between populations in the Balkans and western Anatolia, caused by the barriers of the intervening seas and the Thracian lowland area, probably led to genetic differentiation and allopatric speciation, dated to the early Pleistocene (Kantor & al., 2023). Although only a few samples of C. acris were included in the present study, the sister species relationship between C. anatolica and C. acris in both nuclear and plastome data argues for vicariance rather than long-distance dispersal; indeed, the vicariance scenario is supported by our ongoing RADseq study with thorough sampling of C. acris ( Šlenker & al., unpub.).…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations